Masjid Tuha Indrapuri as an Open History Laboratory: A Qualitative Study of Heritage Site Utilization in Inquiry-Based Islamic History Education at the Higher Education Level - Muhjam Kamza (EDUPEDIA Publisher, 2026)
Purpose – This study examines the utilization of Masjid Tuha Indrapuri as an open history laboratory in inquiry-based Islamic history education at the higher education level in Aceh, Indonesia, with the aim of developing a replicable conceptual model for heritage site-based learning. Methodology – A descriptive qualitative design with an embedded case study strategy was employed over eight months (March–October 2024). Data were collected through passive participant observation (10 sessions), in-depth interviews with six lecturers, 24 purposively selected students, two site managers, and one local historian, alongside document analysis. Trustworthiness was established through source triangulation, methodological triangulation, and member checking. Data saturation was confirmed at the point of theoretical redundancy across participant groups. Findings – The site's tri-layered historical complexity generates authentic open questions that catalyse historical inquiry. A structured three-phase inquiry model qualitatively indicated enhanced critical thinking and historical reasoning among students. Key constraints include limited bilingual interpretive infrastructure, insufficient site-based pedagogical competency, logistical barriers, and the absence of formal academic visitation protocols. Identified benefits encompass strengthened historical consciousness, higher-order historical thinking, reinforced Islamic identity, and foundational research competencies. Novelty – A four-component conceptual model integrating site potential, pedagogical design, facilitator competency, and institutional support is proposed as a replicable framework for Islamic heritage site-based learning with contemporary inquiry-based pedagogy and explicit institutional enabling conditions. Significance – This study benefits history educators, heritage site managers, institutional policymakers, and curriculum developers seeking to integrate cultural heritage into higher education pedagogy across Indonesia and beyond.